Advancing fetal therapy in the United Kingdom. Issue 3 (March 2020) - Sacco, Adalina; David, Anna L.
Abstract: Fetal therapy is a rapidly advancing sub-specialty, encompassing direct fetal treatment or the administration of substances to the mother to achieve fetal benefit. The goal of all fetal therapies is to improve the prognosis for a condition where there is evidence of pathology developing in utero. In this article we briefly examine all major types of fetal therapy and their current evidence.